2017
DOI: 10.1002/mnfr.201600632
|View full text |Cite
|
Sign up to set email alerts
|

Chicoric acid attenuate a nonalcoholic steatohepatitis by inhibiting key regulators of lipid metabolism, fibrosis, oxidation, and inflammation in mice with methionine and choline deficiency

Abstract: CDE and chicoric acid may be effective in the treatment of NAFLD and NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…Along with its hypoglycemic effect, there are reports of chicoric acid having other functional properties, such as antioxidation, anti-inflammation, and anti-fatty liver activities (63,84). Chicoric acid has been considered a potent antioxidant agent due to its effect on inhibiting the accumulation of reactive oxygen species and the generation of inflammatory cytokines, such as nitrogen oxide, interleukin 6, and tumor necrosis factorα (51,64).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with its hypoglycemic effect, there are reports of chicoric acid having other functional properties, such as antioxidation, anti-inflammation, and anti-fatty liver activities (63,84). Chicoric acid has been considered a potent antioxidant agent due to its effect on inhibiting the accumulation of reactive oxygen species and the generation of inflammatory cytokines, such as nitrogen oxide, interleukin 6, and tumor necrosis factorα (51,64).…”
Section: Discussionmentioning
confidence: 99%
“…Chicoric acid has been found to reduce high-fat-diet-induced weight gain in mice (63,64). This was in part via the inhibition of peroxisome proliferator-activated receptorγ (PPARγ) and CCAAT/enhancer binding protein α (C/EBPα), two critical transcription factors in adipocyte differentiation and lipid accumulation, while increasing the secretion of adiponectin (64).…”
Section: Chicoric Acid and Lipid Metabolism And Liver Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cichoric acid is a hydroxycinnamic acid, an organic compound of the phenylpropanoid class, which occurs in a variety of plant species. The oral administration of chicoric acid (10 and 30 mg/ kg) daily for 4 wk reduces the OS by upregulating antioxidant enzymes and decreases the inflammation by inhibiting pro-inflammatory cytokines and NF-κB activation in mice fed with a methionine-and choline-deficient diet [131]. In addition, chicoric acid reduces the fibrosis, apoptosis, and lipogenesis-related gene expression and increases the AMPK activation.…”
Section: Other Compoundsmentioning
confidence: 99%
“…It contains a large amount of bioactive compounds including various hydroxycinnamic acids (HCAs) such as chlorogenic acid, 3,5-di-O-caffeoylquinic acid (3,, chicoric acid and caftaric acid. Several previous studies have reported that C. denticulatum extracts have high anti-oxidative, anti-fatty liver and anti-obesity properties [5][6][7][8], and health functional foods for improving liver function have also been produced using the extract of C. denticulatum. One of the ecological characteristics of C. denticulatum is its sensitivity to the water condition around the root zone with soft rot diseases in the leaf often occurring under conditions of excessive water with frequent rainfall during summer.…”
Section: Introductionmentioning
confidence: 99%